PERANAN DESAIN PARIWARA (IKLAN) DI ERA GLOBALISASI - Sugiharjanto, Asto Adi (KEMADHA, 2012)
Today, the term often heard of Visual Communication Design , in our daily lives. Actually, Visual Communication Design is the development of advertising art and graphic design. Visual Communication Design is a sense of visual design  language of  the disclosure of  ideas or messages conveyed  through  visual  forms  to  the  recipient  (target  audience). Among  them  is  a  form  of  visual  images,  symbols,  symbol,  color, illustration and art of writing (typography). The process of delivering visual messages will  be  delivered  to  audience with  communicative, creative,  innovative, effective, and efficient  through various  forms of media  for  specific purposes.